2017
DOI: 10.1111/cen.13445
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 3 receptor antagonism decreases gonadotropin and testosterone secretion in healthy men

Abstract: These data demonstrate a central role for NKB/NK3R in the physiological regulation of reproductive function in men, and that this is functionally upstream of kisspeptin-mediated GnRH secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…28 Insulin raises testosterone 29 30 providing a pathway from GnRH1 to IHD. Other potential drivers of GnRH1 include neurokinins, 31 32 nitric oxide, 33 aspartate/glutamate, 34 35 gamma-aminobutyric acid 36 and dynorphin. 37 Notably, a common feature of several successful treatments for IHD is suppression of the male reproductive axis, including spironolactone, a known anti-androgen, statins, 38 digoxin, 39 nitric oxide 40 and some hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…28 Insulin raises testosterone 29 30 providing a pathway from GnRH1 to IHD. Other potential drivers of GnRH1 include neurokinins, 31 32 nitric oxide, 33 aspartate/glutamate, 34 35 gamma-aminobutyric acid 36 and dynorphin. 37 Notably, a common feature of several successful treatments for IHD is suppression of the male reproductive axis, including spironolactone, a known anti-androgen, statins, 38 digoxin, 39 nitric oxide 40 and some hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…Proof‐of‐principle studies have demonstrated that kisspeptin administration can increase LH pulse frequency and LH secretion in obese men with low testosterone . Conversely, administration of a neurokinin receptor 3 antagonist decreased gonadotrophin and testosterone secretion in healthy men …”
Section: What Are the Mechanisms Underlying The Obesity‐associated Hpmentioning
confidence: 99%
“…27 Interestingly, while NKB potently stimulates LH release under physiological sex steroid levels in rodents, 26,28,[30][31][32][33][34] sheep, [35][36][37][38][39][40] goats, [41][42][43] cattle, 44 and nonhuman primates, [45][46][47] its gonadotropin-stimulating role is not observed in adult healthy men 48 or women in the follicular phase. 49 Nonetheless, NK3R antagonists decrease overall circulating LH levels and LH pulsatility in humans, [50][51][52][53] suggesting that the role of NKB to elicit kisspeptin/GnRH pulses is conserved in all species, but the optimization of the delivery method and/or concentration of the NK3R agonists is required to observe a stimulation of LH release in humans.…”
Section: New Advances On the Gonadotropin Release Activity Of Tachykimentioning
confidence: 99%